Study on occupational performance of the primary school children with special needs - Khin Nyein Yin; Chin Suliong; Voo, Siew Ching (Universiti Malaysia Sabah, 2012)
Children's occupations are self-care, play, social participation and education. Their performance can be impaired by physical, developmental, sensory, attention and or learning challenges. In developed countries school-based therapy services are being provided for the school children with special needs. The evidence for the needs of these services in Malaysia is timely to be explored.This study aimed to investigate the occupational performance of the primary school children with special needs. This exploratory cross sectional study included 6 to 12 year old 121 children from special education program of 4 primary schools. Motor-Free Visual Perceptual Test 13 _ed (MVPT),5th,ed Beery-Buktenica Developmental Test of Visual Motor Integration (Beery-VMI), Test of Gross Motor Development - 2(TGMD-2), Test of hand writing Skills-Revised (THS-R) and School Function Assessment (SFA) were carried out to assess their occupational performance.Children with intellectual disability, autism, attention deficit hyperactive disorder, Down syndrome, speech impairment, visual impairment, hearing impairment and specific learning disorder were included. Results showed that 69.5% of the children scored low average to very low in MVPT-3; 69.4% scored below average to very low in Beery-VMI; 73.6% were with below age level raw score in TGMD-2; 72.8% were in below average in THS-R and 81 % were with below criterion cut off score in school function participation. Relationship was found between gross motor skill, VMI and visual perception to school function and VMI and visual perception to hand writing skill. The results revealed the needs of school-based therapy and other rehabilitation services in the school system. Early intervention program to improve motor skill, visual perception and visual motor integration is important for the preschool children with special needs regarding the occupational performance improvement in their school age.